Viability and development of Ascaridia galli eggs recovered in artificial media followed by storage under different conditions. (2020) - Feyera, T.; Ruhnke, I.; Sharpe, B.; Elliott, T.; Campbell, D.L.M.; Walkden-Brown, S.W.
Abstract: Eggs oviposited by Ascaridia galli females in artificial media are commonly used as a source of infective material. We investigated the rate of egg production by cultured mature females ( n = 223), and changes in egg viability under different storage and incubation conditions. Eggs recovered after 1, 2 or 3 days of culture were subjected to either (1) storage in water at 4°C (1, 4 or 8 weeks) followed by incubation in 0.1 N H2 SO4 at 26°C (2, 4 or 6 weeks); or (2) prolonged storage at 4°C (up to 14 weeks). Egg development and viability was assessed by morphology coupled with a viability dye exclusion test of hatched larvae. Of the 6, 044 eggs recovered per mature female 49.2, 38.5 and 12.3% were recovered on days 1, 2 and 3 of worm incubation respectively with similar initial viability (≥99%) between days. Eggs recovered on different days had only minor differences in viability after storage. The prolonged storage period at 4°C significantly affected both viability and embryonation ability resulting in decline in viability of 5.7–6.2% per week. A smaller but significant decline in egg (2.0%) and hatched larval (1.4%) viability per week of incubation at 26°C was also observed. We conclude that storage and incubation conditions, not the day of egg recovery, are the main factors affecting A. galli egg viability. Our findings indicate that under aerobic conditions storage at 26°C may be preferable to 4°C whereas other studies indicate that under anaerobic conditions storage at 4°C is preferable.